Microstructure based finite element simulation of JCO forming process for pipeline X65 - Thianngoen, Wut; Kingklang, Saranya; Uthaisangsuk, Vitoon (Journal of Metals, Materials and Minerals, 2015)
In recent years, strong increases in energy demand have become the most important issue in every section. High strength pipeline steels make large contribution to cost reduction for fuel transportation in oil and gas industries due to their great combination of optimal strength and toughness properties. Mechanical properties of pipeline steel tubes are significantly influenced by their microstructure characteristics, which in turn are controlled by the production. In this work, the JCO forming process of gas pipeline tube made of hot–rolled steel grade X65 with ferrite/pearlite microstructure was investigated by means of a FE multi–scale modeling approach. Three different scales including the nano–scale of a ferrite–cementite bi-lamella of pearlite, pearlite/ferrite microstructure on the micro–scale and macro–scale tube were considered. Firstly, local mechanical properties of the X65 steel were examined, in which steel specimens were heated up to austenitization temperature and cooled down to room temperature with high and low cooling rate. Obtained microstructures from both conditions represented material in the center and at the skin of the tube. Stress–strain responses of both different zones were determined by tensile test. Subsequently, FE representative volume element (RVE) models were generated taking into account existing phases and morphologies. Effective flow stress curve of pearlite was predicted by the nano–scale model. In the micro–scale RVE, pearlite with different morphologies distributed in a ferritic matrix was modeled. It was found that stress–strain curve of the X65 steel described by the micro–scale model agreed well with experimental flow curve. Then, two FE simulations of the JCO forming were carried out, by which one was defined with the same microstructure for all area of the tube and other incorporated different microstructures for the skin and center area of the tube. Obviously, the most critical stresses on the formed tube calculated by both models were deviated. Finally, RVE simulations were carried out for the skin and center area of the tube subjected to the JCO forming process. Stress and strain distribution in the microstructure of the X65 steel tube could be evaluated and discussed.